Intensitas Penggunaan Instagram Versus Tanggung Jawab Belajar Siswa SMK - Hana Eva Riani; Naharus Surur; Ma'rifatin Indah Kholili (Jurnal Psikoedukasi dan Konseling, 2022)
Abstract: This study is a correlational study to determine the correlation between two variables, namely the intensity of using Instagram social media and learning responsibility. The theory used in this study is the Uses and Gratification Theory (UGT), in which there are aspects of the intensity of the use of social media. Methods of data analysis using product-moment correlation analysis of 63 respondents. The results showed a negative relationship between the intensity of using Instagram social media and learning responsibility and had a low correlation with a correlation coefficient r of -0.263 and a p-value of 0.037 (0.037 <0.05). This means that the higher the intensity of using Instagram social media, the lower the learning responsibility of students.